Imperfect competition in the labour market - Manning, Alan (London, 2010)
"It is increasingly recognized that labour markets are pervasively imperfectly competitive, that there are rents to the employment relationship for both worker and employer. This chapter considers why it is sensible to think of labour markets as imperfectly competitive, reviews estimates on the size of rents, theories of and evidence on the distribution of rents between worker and employer, and the areas of labour economics where a perspective derived from imperfect competition makes a substantial difference to thought."